STRATEGI POSISI MEREK "RAPOT" DALAM MENGHADAPI PERSAINGAN PODCAST HIBURAN DI SPOTIFY INDONESIA - Marsyifah Jannatu Adnindyani (2022)
One of the content that is currently in demand by the public is Podcast. Rapot is one of the podcasts that is currently at the top of the arts & entertainment genre. In the current podcast phenomenon, a podcaster or group of podcasters not only need to think about the quality of the content, but also apply the right strategy to be able to compete and survive as a podcaster in the Indonesian podcast industry which continues to grow, especially on the Spotify platform. The purpose of this research is to find out the brand positioning strategy that Rapot does in the face of entertainment podcast competition on Spotify Indonesia. The research method used is qualitative with a case study approach. Data collection techniques were carried out by direct interviews with related informants and documentation. Based on the results and discussion of the research that has been obtained, the researcher has analyzed it with the SOSTAC model. In carrying out the strategy, Rapot has content other than regular content, namely content that is different from other podcasters, for example, such as Mau Gak Mau, Obral (Obrolan Ngasal), TTD (Tanya-Tanya Dong), Rapot Anti Repot, Dopamin (Doa Pemirsa Kita Aamiin-in). Another uniqueness is in the tactics stage that is used is not eliminating the "image" in the cover of each personnel in each episode which is the hallmark of the cover.